Nurse Leadership in Disaster Preparedness in 5 Community Health Centers in the Ende Regency City - Budiana, Irwan; Patmawati, Try Ayu; Sekunda, Maria Salestina (International Journal of Natural and Health Sciences, 2024)
Nurses have a very strategic role in reducing risk. This research aims to determine the relationship between nurse leadership and disaster preparedness. The research design used in this research is descriptive analytic with a cross sectional approach. This research was carried out at the Community Health Center from January to October 2023. The population in this study were all nurses at the Ende Regency. Sampling was taken using a non-probability sampling technique, namely purposive sampling. Data were processed using SPSS software in two stages, namely descriptive analysis and bivariate analysis. The research results show that leadership is in the good category with a p value (0.90). Nurses in general are not prepared to be leaders, especially in disaster preparedness